2008
DOI: 10.1007/s00122-008-0712-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and QTL analyses of seed dormancy and preharvest sprouting resistance in the wheat germplasm CN10955

Abstract: The inheritance and genetic linkage analysis for seed dormancy and preharvest sprouting (PHS) resistance were carried out in an F8 recombinant inbred lines (RILs) derived from the cross between "CN19055" (white-grained, PHS-resistant) with locally adapted Australian cultivar "Annuello" (white-grained, PHS-susceptible). Seed dormancy was assessed as germination index (GI7) while assessment for preharvest sprouting resistance was based on whole head assay (sprouting index, SI) and visibly sprouted seeds (VI). Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 39 publications
1
72
0
1
Order By: Relevance
“…Noda et al (2002) investigated another ABA responsive gene located on the long arm of chromosome 4A. QPhs.spa-4A, located in interval barc170-gwm397-wmc617a on 4A, is in a region associated with dormancy and preharvest sprouting resistance in numerous other QTL studies of hexaploid wheat (Flintham et al 2002;Torada et al 2005;Mares et al 2005;Tan et al 2006;Ogbonnaya et al 2008;Imtiaz et al 2008;Munkvold et al 2009;Rasul et al 2009;Kulwal et al 2010;Singh et al 2010Singh et al , 2012Lohwasser et al 2013). The locus was also identified in tetraploid ) and diploid (Nakamura et al 2007) wheat populations, and in an association mapping study (Kulwal et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Noda et al (2002) investigated another ABA responsive gene located on the long arm of chromosome 4A. QPhs.spa-4A, located in interval barc170-gwm397-wmc617a on 4A, is in a region associated with dormancy and preharvest sprouting resistance in numerous other QTL studies of hexaploid wheat (Flintham et al 2002;Torada et al 2005;Mares et al 2005;Tan et al 2006;Ogbonnaya et al 2008;Imtiaz et al 2008;Munkvold et al 2009;Rasul et al 2009;Kulwal et al 2010;Singh et al 2010Singh et al , 2012Lohwasser et al 2013). The locus was also identified in tetraploid ) and diploid (Nakamura et al 2007) wheat populations, and in an association mapping study (Kulwal et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In several earlier studies, QTL for PHST/dormancy have also been detected on wheat chromosome 4AL Kato et al, 2001;Mares and Mrva, 2001;Mares et al, 2005;Chen et al, 2008;Ogbonnaya et al, 2008;Rasul et al, 2009;Nakamura et al, 2007;Singh et al, 2010;Lohwasser et al, 2005;Munkvold et al, 2009;Imtiaz et al, 2008). In wheat the three homoeologues of the GA20-oxidase gene TaGA20-ox1 (involved in gibberellin biosynthesis, controlling PHST/seed dormancy) have also been mapped to chromosomes 5BL, 5DL and 4AL (Appleford et al, 2006).…”
Section: G E N E T I C S P R O V I S I O N a L P U B L I S H I N Gmentioning
confidence: 94%
“…In earlier studies, grain dormancy has been shown to contribute to enhanced resistance to pre-harvest sprouting (Mares et al, 2009;Osa et al, 2003;Nakamura et al, 2007;Lohwasser et al, 2005;Torada et al, 2005;Ogbonnaya et al, 2008;Singh et al, 2010;Chen et al, 2008;Mares et al, 2005;Kottearachchi et al, 2008;Imtiaz et al, 2008;Munkvold et al, 2009;Fofana et al, 2009). This observation is confirmed by the results of the present study showing clustering of individual original QTLs for PHST and grain dormancy into a single cluster during meta-QTL analysis.…”
Section: Relationship Between Phst and Dormancymentioning
confidence: 99%
“…그러나, 인삼의 경우 외부 형태적 특성에 의한 유전자원의 평가는 유 전자형과 환경 간의 상호작용과 해가림 시설 등 재배방법에 따라서 표현형이 달라지기 때문에 적당하지 않다. 이러한 문 제점을 보완하기 위하여, 환경에 영향을 받지 않는 DNA 마 커를 이용한 유전적 다양성 분석과 품종 판별 에 관한 연구가 진행되어, 오이 (Bernet et al, 2003), 대청 , 유채 (Tommasini et al, 2003), 고추 (Kwon et al, 2005), 밀 (Noil et al, 2008), 사과 (Cho et al, 2010 (Wu and Tanksley, 1993;Saghai-Maroof et al, 1994;Morgante et al, 1995;Ogbonnaya et al, 2008).…”
unclassified